Respuesta del cultivo de cacao (Theobroma cacao l.) A la poda y fertilización orgánica y química. - Alcívar Valdez, Josefa Patricia (2016)
This research was conducted from October 2013 to July 2014 in the area of cocoa of the ESPAM - MFL , located in Calceta - Manabí - Ecuador , the main objective was to study the response of cocoa to different levels of pruning and the application of chemical and organic fertilization. We used a randomized block design with three replications, with two levels of pruning (15 and 30%) and three types of fertilization (Formulated. 354 g Urea + 116 g. of 10-30-10 / plant ; Conventional: 10-30-10 300 g / plant and organic : 400 g of organic fertilizer Biogrowth / plant) . The results indicate that pruning levels (15 and 30 %), and three types of fertilization (formulated , conventional and organic) did not influence the number of healthy buds and infected by witches' broom .In relation with the performance, pruning levels evaluated showed no significant effect . In contrast , we detected significant differences between the types of fertilization, with the conventional fertilization which showed the highest yield 20 quintals/ ha of dry cacao, followed by organic fertilization with 16 quintals / ha and formulated fertilization showed the least yield 10 quintals / ha of dry cacao. Considering the results, we recommended to design fertilization plans based on analysis of soil and the requirements of the crop.